2014
DOI: 10.1073/pnas.1313826111
|View full text |Cite
|
Sign up to set email alerts
|

A dynamically assembled cell wall synthesis machinery buffers cell growth

Abstract: Assembly of protein complexes is a key mechanism for achieving spatial and temporal coordination in processes involving many enzymes. Growth of rod-shaped bacteria is a well-studied example requiring such coordination; expansion of the cell wall is thought to involve coordination of the activity of synthetic enzymes with the cytoskeleton via a stable complex. Here, we use singlemolecule tracking to demonstrate that the bacterial actin homolog MreB and the essential cell wall enzyme PBP2 move on timescales orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
90
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(100 citation statements)
references
References 41 publications
10
90
0
Order By: Relevance
“…Consistent with our simulations, fluorescently tagged monofunctional transpeptidase PBP2a of Bacillus subtilis moves circumferentially around cells (28,29), and PBP2 of E. coli was shown by bacterial two-hybrid and chemical crosslinking assays to interact with PBP1A in vitro and in the cell (52). A recent study reported, however, that fluorescently-tagged PBP2 of E. coli moves with a diffusive behavior, which is not affected by A22 treatment (70), while the same treatment causes fluorescently-tagged Caulobacter crescentus PBP2 to lose its spiral localization pattern (71). Thus, additional study is needed to resolve these discrepancies.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with our simulations, fluorescently tagged monofunctional transpeptidase PBP2a of Bacillus subtilis moves circumferentially around cells (28,29), and PBP2 of E. coli was shown by bacterial two-hybrid and chemical crosslinking assays to interact with PBP1A in vitro and in the cell (52). A recent study reported, however, that fluorescently-tagged PBP2 of E. coli moves with a diffusive behavior, which is not affected by A22 treatment (70), while the same treatment causes fluorescently-tagged Caulobacter crescentus PBP2 to lose its spiral localization pattern (71). Thus, additional study is needed to resolve these discrepancies.…”
Section: Discussionsupporting
confidence: 89%
“…In Escherichia coli, multiple proteins have been suggested to interact with MreB, including the penicillin binding protein (PBP) cell wall synthesis enzymes and RodZ, an integral membrane protein that directly binds MreB (8)(9)(10)(11). PBP2 inhibitors block MreB rotation (5) but the PBP2 protein does not have similar dynamics to MreB (12), thus ruling out PBP2 as the major linker between MreB rotation and cell wall synthesis. In contrast, we discovered that RodZ displays similar dynamics to MreB.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, some of the cellwall-synthesis enzymes have been seen to move in a similar manner as MreB filaments in the Gram-positive B. subtilis (Garner et al 2011;Domínguez-Escobar et al 2011), supporting the hypothesis of physical interaction. In Gram-negative E. coli, at least one important synthesising enzyme, the transpeptidase PBP2, moves rapidly and diffusively, showing no processivity on the sub-second time scale (Lee et al 2014), thus suggesting a more transient interaction of the cell-wall synthesis proteins. Tuson et al (2012) finds that the timescales at which disrupting MreB affects cell wall elasticity are similar to the growth time, in consistence with this interpretation.…”
Section: Necessity For Regulationmentioning
confidence: 99%